Impacto da terapia com a hidroxiuréia e dos haplóticos no perfil oxidativo na anemia falciforme - Santos, Bruna Stefânia Carvalho dos (2011)
The sickle cell anemia is one of the most common genetic disorders in our country. The -globin haplotypes are associated with the clinical heterogeneity of the disease. Individuals with sickle cell disease are subjected to high levels of oxidative stress. Hydroxyurea (HU) has been used as treatment and it increases the levels of fetal hemoglobin having an action antioxidant. The study aimed to investigate the impact of the use of HU and haplotypes in the oxidative status in patients with sickle cell anemia. Samples from 64 patients treated at the University Hospital Walter Cantídio - HUWC and the control group of 20 individuals without hemoglobinopathies. Patients were stratified into groups: the first one using HU > 1 year, the second using HU ≤ 1 year and the third using of HU (SHU). Confirmation of the diagnosis and analysis of haplotypes were performed by molecular study. The measurements of nitrite (NO2-), malonaldehyde (MDA), glutathione peroxidase (GSH-Px), catalase (CAT), glutathione total (GSSG+GSH), oxidized (GSSG) and reduced (GSH) and the ratio GSSG/GSH (glutathione oxidized/reduced) were performed by spectrophotometry. Mean levels of NO2- and MDA were shown to be higher in SHU group, being significant only for MDA (p < 0,05). The assessment of oxidative stress in relation to haplotypes showed that the population without the use of HU levels of NO2- and MDA were similar between groups, with an insignificant increase of GSH-Px in the Bantu/n compared with Benin/n and index GSSG/GSH in the Benin/n compared with Bantu/n. In the population using the HU there was a nonsignificant increase in the levels of NO2- in the Bantu/n compared with Benin/n with similar results between groups of MDA and a significant increase in GSH-Px (p <0.03) in the Benin/n compared with Bantu/n. The results of CAT were similar between groups. The ratio of GSSG/GSH was higher but not significant in the Bantu/n compared to Benin/n. The results of this study support the hypothesis that patients with the sickle cell anemia have a state hiperoxidativo products with high levels of oxidative stress and decreased antioxidant status and that of hydroxyurea had an impact on oxidative stress. However, regarding the impact of the haplotypes in oxidative stress, further studies with a larger sample should be recommended to confirm our results, considering that the group of patients not treated with HU was lower than the group of patients using HU, the which may have interfered in the statistical analysis of results.